Linguistic distance affects executive performance in trilinguals - M. Nelyubina; A. Myachykov; J. Abutalebi; Y. Shtyrov; F. Gallo (Acta Psychologica, 2025)
Recent research has highlighted potential benefits associated with bilingualism for overall cognitive efficiency and health. One understudied dimension of the bilingual experience is linguistic distance (LD), a measure defining how (dis)similar two given languages are. The previous study has explored the role of LD as a modulator of bilingualism-induced neurocognitive consequences in aging individuals. However, this has scarcely been investigated in young populations. To fill this gap, we examined the impact of LD between second and third language on executive functioning - as indexed by Flanker task performance - in a cohort of young adults (18–29 years old). The results show that L2-L3 LD dynamically modulates multilingualism-induced effects on inhibitory executive control performance in young trilinguals, with a pattern of LD contribution to executive functioning characterized by a two-stage trajectory. In the early stages of multilingual experience, distant non-native languages are associated with maximal cognitive benefits, expressed in faster Flanker reaction times, and explained by a larger cognitive effort in acquiring a distant language. However, as multilingual experience accrues, closer language pairs predict enhanced cognitive processing, likely driven by the more demanding effort of juggling more similar lexicons and grammars.